SwiftTrip: Your Smart Travel Companion for Effortless Planning and Memorable Journeys - R. Regin; Rajest , S. Suman (International Journal on Human-Computing Studies, 2024)
This paper presents "SwiftTrip," an innovative tool designed to enhance travel planning by integrating location, activity, weather, and packing considerations. As travel becomes increasingly spontaneous, there is a need for comprehensive solutions that cater to dynamic travel environments. "SwiftTrip" addresses this gap by offering detailed vacation itineraries, weather forecasts, and customized packing lists. The system utilizes climate patterns to suggest optimal travel routes and weather-sensitive recommendations for attractions and activities. Advanced algorithms analyze meteorological data to generate personalized packing lists, ensuring travelers are prepared for varying weather conditions. By providing current and forecasted weather data, including temperature, precipitation, and wind speed, "SwiftTrip" aims to make travel planning more informed and enjoyable, ultimately enhancing the travel experience in a rapidly changing environment.